Constructing 2D Porous Graphitic C3N4 Nanosheets/Nitrogen‐Doped Graphene/Layered MoS2 Ternary Nanojunction with Enhanced Photoelectrochemical Activity. (29th August 2013) - Hou, Yang; Wen, Zhenhai; Cui, Shumao; Guo, Xiaoru; Chen, Junhong
Abstract : A 2D porous graphitic C3 N4 nanosheets/nitrogen‐doped graphene/layered MoS2 ternary nanojunction is synthesized using a simple pyrolysis process followed by a hydrothermal treatment. The 2D ternary nanojunction exhibits significantly enhanced photoelectrochemical and photocatalytic activities due to the large contact area, efficient light absorption, and rapid charge separation and transport.